Design and Construction of a Coconut Coir Chopping Machine Based on a Three-Phase Induction Motor with Frequency Variation for Cocofiber Quality Optimization - Alvin Saputra; Yudi Siswanto; Hendi lilih wijayanto (CV. Edujavare Publishing, 2026)
Coconut coir is an abundant by-product of coconut processing that remains underutilized, particularly in Bahodopi District, Morowali Regency. Coir chopping is still carried out manually, which is time- and labor-intensive and produces uneven results. This study aims to design and build a robust, easy-to-operate coconut coir chopping machine capable of efficiently converting coir into cocofiber. The engineering method was applied, comprising literature study, design using SolidWorks, frame strength simulation, material selection, assembly, and testing. The machine is driven by a three-phase induction motor (1400 rpm, 50 Hz) equipped with an inverter, allowing the blade rotation speed to be varied at 15, 30, and 50 Hz. Testing used approximately 3 kg of dry coir for each variation. The results show that the machine can chop coir at a capacity of 180 kg/hour, with the best result—fine and even—obtained at 30 Hz. Static simulation of the frame under an 800 kgf load produced a maximum stress of 374.421 MPa and a minimum safety factor of 0.939, indicating the need to reinforce the critical points of the frame. This machine is expected to help the Bahodopi community process coir more easily and to create new economic opportunities